Measurement of the proton-air cross section at √s=57 TeV with the Pierre Auger Observatory. - Abreu, P; Aglietta, M; Ahn, E; Albuquerque, I; Allard, D; Allekotte, I; Allen, J; Allison, P; Almeda, A; Alvarez Castillo, J; Alvarez-Muñiz, J; Ambrosio, M; et al. (2012)
We report a measurement of the proton-air cross section for particle production at the center-of-mass energy per nucleon of 57 TeV. This is derived from the distribution of the depths of shower maxima observed with the Pierre Auger Observatory: systematic uncertainties are studied in detail. Analyzing the tail of the distribution of the shower maxima, a proton-air cross section of [505±22(stat)(-36)(+28)(syst)] mb is found.